Efficacy and Safety of Mechanical Insufflation–Exsufflation in Invasively Ventilated Critically Ill Adults: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials - Zhiqun Liu; Guiling Liao; Hui Wen; Xiaotong Han; Maiying Fan; Shuzhen Mao; Xiaohua Liu; Huan Wan (Nursing in Critical Care, 2026)
ABSTRACT Background Mechanical insufflation–exsufflation (MI–E) is increasingly used in invasively ventilated adults in the intensive care unit (ICU), yet its therapeutic efficacy and safety remain uncertain due to inconsistent evidence. Aim To synthesize evidence on the clinical efficacy and safety of MI–E in this population and to examine methodological and clinical heterogeneity underlying reported outcomes. Study Design A systematic review and meta‐analysis of randomized studies (including RCTs and randomized crossover trials), conducted following PRISMA guidelines, with risk of bias assessed using the Cochrane risk‐of‐bias tool. Results Five randomized controlled trials involving 310 patients were included. Meta‐analysis showed that mechanical insufflation–exsufflation (MI–E) significantly increased sputum clearance (SMD = 0.63, 95% CI, 0.32–0.93; p < 0.00011; I 2 = 38%) without affecting oxygenation (MD = 0.28, 95% CI, −0.53 to 1.09; p = 0.50; I 2 = 9%). Data on respiratory mechanics, ventilation duration and ICU stay could not be pooled. No serious adverse events were reported. Conclusions MI–E significantly improves sputum clearance in invasively ventilated critically ill adults, with no severe adverse events reported in the included studies. Its effects on other outcomes remain inconclusive due to limited data and heterogeneity. Standardized protocols and larger trials are needed. Relevance to Clinical Practice Clinicians may consider MI–E as an adjunct for respiratory secretion management. Application should be guided by structured patient assessment and individualized parameter adjustment. Future research should standardize interventions and target well‐defined patient subgroups to inform clear practice guidelines. Trial Registration The review protocol was registered in the International Prospective Register of Systematic Reviews, with registration number CRD42023403299